Risk factors for viral reactivation in patients with overt or occult Hepatitis B Virus infection receiving immunosuppressive treatments: A systematic review and meta-analysis with decision curve analysis. (March 2023) - Rizzo, G.E.M.; Celsa, C.; Enea, M.; Di Maria, G.; Vaccaro, M.; Rancatore, G.; Graceffa, P.; Falco, G.; Calvaruso, V.; Di Marco, V.; Cammà, C.
Abstract : Introduction: Patients with Hepatitis B virus (HBV) infection receiving immunosuppressive treatments are at risk of HBV reactivation (rHBV). Aims: We performed a systematic review with meta-analysis to estimate the risk of rHBV among patients naïve to antiviral prophylaxis and to identify factors associated with rHBV. Methods: Studies of immunosuppressive treatments in HBV patients were identified through literature search using PubMed, MEDLINE, and EMBASE until October 2022. Pooled estimates were obtained using random-effects model. Subgroup analyses were performed according to viral status, drug class and underlying disease. Decision curve analysis(DCA) was used to identify the risk threshold associated with the best net benefit of administering antiviral prophylaxis in HBsAg negative anti-HBc positive patients. Results: Seventy-nine studies (48 retrospective and 31 prospective) were selected, including 9946 patients (1108 HBsAg positive, 8203 anti-HBc positive and 635 isolated anti-HBs positive). Pooled rHBV rate was 6%(95% CI 5-8%; I 2 79%; P<0.001) with a rate of 23%(95% CI 16-31%), 4.6%(95% CI, 3.4-6.1%) and 2.9%(95% CI 1.5-10%) in HBsAg positive, anti-HBc positive and isolated anti-HBs positive patients, respectively. In HBsAg positive patients, the risk for rHBV ranged from 22%(95%CI 11-39%) in patients with autoimmune disease receiving immunosuppressants to 30% (95%CI 5-79%) in patients with cancer receiving chemotherapy. In anti-HBc positive patients with cancer, chemotherapy, targeted-therapy and monoclonal antibodies were associated with risk of rHBV of 9%(95%CI 5-15%), 7%(95% CI 1-43%) and 5%(95%CI 2-10%), respectively; in anti-HBc positive with autoimmune diseases, the risk of rHBV was 3%(95% CI 2-4%), 4%(95% CI 2-8%) and 3%(95%CI 1-13%) for anti-TNFα, other monoclonal antibodies and immunosuppressants, respectively. DCA showed that the risk threshold of rHBV associated with the best net benefit of administering antiviral prophylaxis in anti-HBc positive patients was 7%. Conclusions: The risk of rHBV is highly heterogeneous according to viral status, underlying diseases and drug class. In anti-HBcore positive patients, antiviral prophylaxis should be considered when the risk of rHBV is higher than 7%.